IMPLEMENTING AN ONLINE-BASED KALLIMNI PROGRAM TO IMPROVE MAHĀRAH KALĀM IN THE PANDEMIC OF COVID-19 - Lisa Khillatur Risalah; Machmudah, Umi; Arifa, Zakiyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
An online-based kalam learning program at al-Azhar course institution, which has been implementing an online Arabic language program since before the pandemic of the Covid-19, was the primary focus of this study, which examines the execution of this program during the pandemic. These findings are the result of a form of a qualitative study. Interviews, observation, and documentation are employed to gather data. The data sources for this research include various informants, the implementation process of the online Kallimni program, and al-Azhar course institution papers linked to the online Kallimni program. When it came to analyzing the data, the researchers followed Miles and Huberman's recommendations to reduce the data, visualize it, and make conclusions. Using WhatsApp and Instagram, the online Kallimni program could well be implemented. In this online Kallimni program, the learning is project-based and themed. The online Kallimni program included both motivating and stifling features identified by the researchers. As a result of this study, teachers and students must engage in conversation to master speaking skills (mahārah kalām). Teachers should thus use additional technologies, such as Google Meet, Zoom, or Skype to help students learn speaking skills (mahārah kalām) more diversely and visibly.